The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1002/hep.32622
|View full text |Cite
|
Sign up to set email alerts
|

Limited disassembly of cytoplasmic hepatitis B virus nucleocapsids restricts viral infection in murine hepatic cells

Abstract: Background and Aims: Murine hepatic cells cannot support hepatitis B virus (HBV) infection even with supplemental expression of viral receptor, human sodium taurocholate cotransporting polypeptide (hNTCP). However, the specific restricted step remains elusive. In this study, we aimed to dissect HBV infection process in murine hepatic cells. Approach and Results: Cells expressing hNTCP were inoculated with HBV or hepatitis delta virus (HDV). HBV pregenomic RNA (pgRNA), covalently closed circular DNA (cccDNA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Going further, Zhao et al3 found that some rcDNA did reach the murine nucleus, but disappeared over time without cccDNA production (Figure 1B). Their most striking observation, however, was the nearly complete nuclease resistance of cytoplasmic NC‐borne rcDNA in murine cells, whereas in human cells a substantial fraction of this rcDNA was nuclease sensitive.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Going further, Zhao et al3 found that some rcDNA did reach the murine nucleus, but disappeared over time without cccDNA production (Figure 1B). Their most striking observation, however, was the nearly complete nuclease resistance of cytoplasmic NC‐borne rcDNA in murine cells, whereas in human cells a substantial fraction of this rcDNA was nuclease sensitive.…”
Section: Introductionmentioning
confidence: 82%
“…huNTCP enables HBV entry into murine cells (not explicitly shown), but usually not cccDNA formation. Experiments by Zhao et al [3] to identify the critical step(s) are indicated by white boxes with blue lettering. Artificial delivery of HBV plasmid vectors or cccDNA (not shown) generated all expected RNAs, proteins, and progeny NCs, ruling out transcriptional issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the ability to support HBV cccDNA formation in AML12 cells could be correlated with enhanced destabilization (uncoating) of mature HBV nucleocapsids [ 17 ]. Similarly, some evidence has been presented recently suggesting that the failure to support nucleocapsid uncoating by mouse hepatocytes may also contribute to the inability of mouse hepatocytes to support cccDNA formation during HBV infection after huNTCP expression [ 78 ]. Consistent with the expectation that the DNA repair reactions involved in rcDNA to cccDNA conversion, per se, are highly conserved during evolution, mouse, and even yeast, DNA repair factors can support cccDNA formation from rcDNA mimics [ 78 , 79 , 80 ].…”
Section: The Role Of Hbc In Specifying Hbv Host Tropismmentioning
confidence: 99%
“…Similarly, some evidence has been presented recently suggesting that the failure to support nucleocapsid uncoating by mouse hepatocytes may also contribute to the inability of mouse hepatocytes to support cccDNA formation during HBV infection after huNTCP expression [ 78 ]. Consistent with the expectation that the DNA repair reactions involved in rcDNA to cccDNA conversion, per se, are highly conserved during evolution, mouse, and even yeast, DNA repair factors can support cccDNA formation from rcDNA mimics [ 78 , 79 , 80 ]. Therefore, overcoming the failure of nucleocapsid disassembly in mouse hepatocytes should help to establish a mouse model that can support HBV cccDNA formation and infection.…”
Section: The Role Of Hbc In Specifying Hbv Host Tropismmentioning
confidence: 99%